L1–L2 differences in the L2 classroom: Anticipating Anglophone learners' difficulties with French pronoun interpretation. (March 2019) - Shimanskaya, Elena; Slabakova, Roumyana
In this article, we address the issue of targeted instruction on interpretive contrasts between native and second-language grammatical meanings. Such mismatches are predicted to create challenges for learners. We illustrate this with French and English pronouns. In French, clitic pronouns ( le, la ) point to human as well as inanimate referents, while English pronouns distinguish between human ( him, her ) and inanimate ( it ) referents. While other grammatical differences between English and French pronouns are taught, this interpretive mismatch attracts less attention in instructional materials. We review the pedagogical literature and report the results of a study investigating this knowledge in Anglophone learners of French as a second language (L2). We document that the mismatch is indeed challenging, particularly to beginning learners, and propose ways to overcome this difficulty.